Epidemiology of invasive fungal infections in lung transplant recipients in Western Australia. Issue 3 (16th April 2019) - Chang, Andrew; Musk, Michael; Lavender, Melanie; Wrobel, Jeremy; Yaw, Meow‐Chong; Lawrence, Sharon; Chirayath, Shiji; Boan, Peter
Abstract: Background: Invasive fungal infections (IFI) are common after lung transplantation with reported incidence of 8.1% to 16% at 12 months post‐transplant, and 3‐month all‐cause mortality after IFI of 21.7%. Methods: We performed a retrospective study of IFI and fungal colonization in lung transplants (LTs) from November 2004 to February 2017. Results: 137 LTs were followed for a median 4.1 years (IQR 2.1‐6.2 years). In addition to nebulized amphotericin for the transplant admission to all LTs, systemic mold‐active azole was given to 80/130 (61.5%) LTs in the first 6 months post‐transplant, 57/121 (47.1%) in the period 6‐12 months after transplant, and 93/124 (75%) in the period more than 12 months post‐transplant. Mold airways colonization was found in 81 (59.1%) LTs before and 110 (80.3%) LTs after transplantation. There were 13 IFIs for an overall incidence of 2.1 per 100 person‐years, occurring at a median 583 days (IQR 182‐1110 days) post‐transplant, a cumulative incidence of 3.8% at 1 year, 7.6% at 3 years and 10.1% at 5 years post‐transplant. All‐cause 3‐month mortality after IFI was 7.7%. Aspergillus species followed by Scedosporium apiospermum and Cryptococcus species were the commonest fungi causing IFI. Conclusions: In our cohort the rate of IFI was comparatively low, likely because of comprehensive early antifungal use and preemptive therapy at any time after transplant. Prospective studies of fungal colonization late after LT are required to determine the risks and benefits of watchful waiting compared to preemptive therapy.